2022
DOI: 10.32714/ricl.10.02.05
|View full text |Cite
|
Sign up to set email alerts
|

Cross-linguistic transfer in academic journal writing: Evidence from lexical bundle analysis in Russian and English

Abstract: Lexical bundles are considered a fundamental feature of academic writing and have been extensively studied by corpus linguists. However, while learner corpus-based studies have noted the differences between first (L1) and second languages (L2) in the production of lexical bundles, few of them have assessed the underlying causes of such differences, particularly regarding cross-linguistic transfer. The present study investigates the use of lexical bundles in professional writing in the field of Educational Psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
0
0
0
Order By: Relevance
“…Similarly, Güngör and Uysal (2020) revealed that non-native Turkish researchers used 50% more lexical bundles than native speakers of English did in their research articles. In her study, Kostromitina (2022) also revealed that L2 English (227) and L1 Russian (264) writing contained more than twice the number of bundles in L1 English writing (83). These finding may be explained by the fact that learners might have utilized bundles with greater frequency in an attempt to produce texts that bore resemblance to academic discourse.…”
Section: Lexical Bundles In Tmpe and Ampementioning
confidence: 88%
See 1 more Smart Citation
“…Similarly, Güngör and Uysal (2020) revealed that non-native Turkish researchers used 50% more lexical bundles than native speakers of English did in their research articles. In her study, Kostromitina (2022) also revealed that L2 English (227) and L1 Russian (264) writing contained more than twice the number of bundles in L1 English writing (83). These finding may be explained by the fact that learners might have utilized bundles with greater frequency in an attempt to produce texts that bore resemblance to academic discourse.…”
Section: Lexical Bundles In Tmpe and Ampementioning
confidence: 88%
“…The findings showed that L2 English retained a small stock of bundles transferred from L1 Spanish (17% of all the bundles in L2 English) and exhibited a considerable percentage of idiosyncratic bundles (the remaining 36% of its bundles). Kostromitina (2022) sought evidence on the cross-linguistic influence on the use of L2 lexical bundles in academic writing by Russian writers. The result suggested an overlap in the use of lexical bundles between L2 English writing produced by Russian speakers and L1 Russian writing, which emphasized the possible L1 transfer.…”
Section: Related Studiesmentioning
confidence: 99%